Recovery of Copper Metal through Reprocessing of Residues from a Hydrometallurgical Plant: An Advance Study - L. M. Shengo; B. K. Kitungwa; C. W. N. Mutiti; J. L. M. Mulumba; F. P. Ilunga (Advanced Aspects of Engineering Research Vol. 13, 2021)
The Chemical of Africa (CHEMAF) is a hydrometallurgical plant that was commissioned in 2001. It produces copper (Cu) cathodes and salts of cobalt (Co) using a process encompassing the sulphuric acid leaching of Cu-Co oxidised ores under reducing conditions (Na2S2O5 or SO2) followed by the leach liquor purification by solvent extraction (SX), electrowinning of copper and the precipitation of Co as hydroxides. The leach liquor is recovered via the thickening of pulps from the ores leaching section and the depletion in valuable metals of the leaching residues by washing inside the counter-current decanters (CCD). The hydrometallurgical residues from Cu production were anciently dumped near the plant. With the increase in the content sulphide minerals in the run of mine (ROM) ores brought about by variations in the mineralogy of the Kalukuluku deposit and considering that the storage of solid residues may result in toxic pollutant release to the environment, the reprocessing of solid residues constitutes a best management option. The present research aims at recovering Cu metal retained in hydrometallurgical solid residues (2.01% Cu and 0.32% Co) and utilizes a process based on the sulphuric acid leaching followed by the recovery of Cu as metal through cementation with iron shavings. After experiments, it has been observed that the leaching of the Cu (? 90%) and Co (86%) succeeded when 150 g of solid residues were stirred (500 rpm) during 90 minutes (at 75°C) in 1 L of an acid solution (H2SO4: 30 g/L) under reducing conditions (Na2S2O5), with the pulp’s redox potential maintained at 330 mV. Consequently, copper was recovered as metal (2.5 g of solids assaying 93% Cu recovered at 86%) when 1 g of iron shavings was stirred during 60 minutes, at room temperature and constant speed (400 rpm), in 250 mL of a metalliferous solution (10.84 g/L Cu and 1.73 g/L Co) prepared through the leaching of solid residues.